Vivekananda, Sarah Farmer, and global spiritual transformations in the fin de siècle. Issue 2 (July 2019) - Harris, Ruth
Abstract: As Swami Vivekananda travelled West at the end of the nineteenth century to propagate what has become known as 'Hindu Universalism', the American Sarah Farmer travelled to Palestine to embrace the new Baha'i faith. This article will ask why both wished to create 'universal' religions, and why they found inspiration at Green Acre, Maine in 1894 in the wake of the Chicago World Parliament of Religions in 1893. Visitors to Green Acre discussed 'divine femininity', engaged with men such as Vivekananda and Abdu'l-Baha, and began to criticize colonial hierarchies in the search for spiritual reconciliation, all concerns which touched on questions of 'Eastern' religion. However, spirituality was not a mere epiphenomenon of larger historical developments. Rather, the 'transformation' discussed here drew on an essentialized notion of 'Eastern wisdom' that contrasted spirituality with materialism, tolerance with intolerance, transcendence with instrumentalism. Yet, such polarized characterizations misjudged the ways in which Baha'i and Hindu Universalism destabilized the very categories of East and West, while retaining a vision of 'Eastern wisdom' untouched by Western corruptions.